Does the age of milk affect its mid-infrared spectrum and predictions - Magro S; Sneddon NW; Costa A; Chiarin E; Penasa M; De Marchi M (Elsevier Ltd, 2024)
Milk of dairy species commonly undergo standardized official analyses, these that may require chemical preservation and transportation to a certified laboratory. In this context, storage duration is an important factor that can potential affect both milk chemical analyses and its mid-infrared spectrum. We analysed milk samples at different time points/ages to assess repeatability and reproducibility of mid-infrared predicted traits (e.g., fat and protein). Using spectral data, we also evaluated the ability of spectroscopy coupled with chemometrics to discriminate samples according to their age. Although the main components of milk remained consistently reproducible across age (days), changes in the spectrum due to sample aging and deterioration of the matrix were detectable. Using a discriminant analysis, we achieved a classification accuracy of 77% in validation. Predicting milk age using mid-infrared spectra is feasible, allowing for sample monitoring within circuits where maximum reliability is needed, e.g., bulk or individual milk samples for legal/official use or payment systems.
Keywords: Cow milk composition; Fraud; Mid-infrared spectroscopy; Repeatability; Storage time; Female; Animals; Milk; Reproducibility of Results; Spectrum Analysis; Phenotype; Spectrophotometry, Infrared; Lactation